2021
DOI: 10.19127/bshealthscience.858331
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Smoking Addiction of Social Approval Needs in University Students: A Structural Equation Modeling

Abstract: Bu çalışmada üniversite öğrencilerinde sosyal onay ihtiyacının sigara bağımlılığı üzerine etkisini derinlemesine araştırmak amacıyla yapısal eşitlik modellemesi kullanılmıştır. Araştırma Erciyes Üniversitesi'nde öğrenim gören 227 öğrenci ile yürütülmüştür. Verilerin toplanmasında tanıtıcı bilgi formu, Fagerström Nikotin Bağımlılık Testi ve Sosyal Onay İhtiyacı Ölçeği kullanılmıştır. Verilerin değerlendirilmesinde bağımsız örneklem t testi, tek yönlü varyans analizi ve Pearson Korelasyon analizi uygulanmıştır. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Battaloğlu İnanç 28 (2015) found that the mean FTND score was 3.08±2.07, and 20.0% of the participants had advanced and 5% had very advanced levels of nicotine addiction. The mean FTND score of the nursing students was found as 3.88±2.34 by Moreno-Coutiñove and Villalobos-Gallegos 54 (2017) and 3.52±2.47 by Evli et al 16 (2021). The reasons why addiction scores are higher than in the literature can be shown as smokers around, encouragement of friends and feeling of curiosity, staying away from family, seeing family as authority, and the sense of autonomy that comes with university life 55 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Battaloğlu İnanç 28 (2015) found that the mean FTND score was 3.08±2.07, and 20.0% of the participants had advanced and 5% had very advanced levels of nicotine addiction. The mean FTND score of the nursing students was found as 3.88±2.34 by Moreno-Coutiñove and Villalobos-Gallegos 54 (2017) and 3.52±2.47 by Evli et al 16 (2021). The reasons why addiction scores are higher than in the literature can be shown as smokers around, encouragement of friends and feeling of curiosity, staying away from family, seeing family as authority, and the sense of autonomy that comes with university life 55 .…”
Section: Discussionmentioning
confidence: 90%
“…Smoking in young people is facilitated and reinforced by certain factors such as individual's age, income, acculturation, stress, and environmental factors including tobacco advertising and ease of purchase of tobacco products [13][14][15] . Starting and continuing to smoke cigarettes in adolescence arises from wanting to feel appreciated, fitting in socially, and through the influence of friends 16 . A person's university years are a period of rapid life changes, new friendships, and social sharing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation